Prevalence of parainfluenza type 3 virus antigens in pneumonic caprine lungs by direct immunofluorescence and immunoperoxidase techniques - Ceribasi, Songul; Ozkaraca, Mustafa; Ozer, Harun; Ceribasi, Ali Osman (Elsevier, 2012)
The purpose of this study was to determine the prevalence of Parainfluenza type 3 (PI-3) virus antigens using direct fluorescent antibody technique (DFAT) and immunoperoxidase (IP) staining of frozen and formalin-fixed paraffin-embedded tissues in pneumonic lungs of goats. An abattoir survey for prevalence of pneumonia in goats was carried out between January and June 2011 in Elazig region. A total of 889 goat lungs were grossly examined, and pneumonic apical and cardiac lobes were detected in only 152 lungs (17.10%). The severity of lesions in apical and cardiac lobes was scored according to the extent of consolidation. The tissues were stained with hematoxylin and eosin. IP and DFAT methods were only performed in tissues with 106 interstitial or fibrinous chronic bronchopneumonia. In conclusion, PI-3 viral antigens were identified at the rate of 44.40% by DFAT and 28.30% by IP in cases of natural chronic bronchopneumonia in goats in Elazig region, and the virus was suggested as one of the important etiological agents in chronic bronchopneumonia in goats. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Parainfluenza-3; Chronic bronchopneumonia; Immunofluorescence; Immunoperoxidase; Goat